The Glycemic Index Value of Hipa 7 and the Determination Method - Handoko, Dody Dwi; Indrasari, Siti Dewi (Kaunia: Integration and Interconnection Islam and Science Journal, 2020)
Carbohydrate content information of food does not enough to describe its physiological effect. Different carbohydrate sources give diverse blood glucose response. The concept of glycemic index (GI) was introduced to fill that gap. It divides food into several classifications according to their postprandial glycemic response. The original method was conducted by observing blood glucose after consuming sample then comparing the result with standard food. Later, miscellaneous in vitro digestion models were developed to mimic the in vivo condition. Rice is one of food types that have various GI which are related to the rice variety and postharvest processing method. There are some varieties that have low or medium GI, the others have higher. Parboiled and brown rice tend to have lower GI compared to their un-parboilled milled rice form. Hipa 7 is hybrid new superior variety that that had been launched by ICRR in 2009 and its milled rice has low glycemic index 49.2. Low glycemic index rice potentially reduced the occurrence of obesity and diabetic mellitus disease.